Pre-Weaning Growth Performance of Boerka (Boer >< Kacang) Crossbred Kids in the Difference Genotype and Birth Types - Lalu Wira Pribadi; Rr. Agustien Suhardiani; Tahyah Hidjaz; M. Ashari; Happy Poerwoto; Rina Andriati; Lalu Ahmad Zaenuri (Jurnal Biologi Tropis, 2022)
Breeding programs to promote the productivity of Indonesian local goats (i.e. Kacang Goats) in various regions have been carried out by cross-breeding with predominant breeds of meat goats in the world such as Boer Goats. Currently, considering that the various genotypes of the cross-bred goat (namely Boerka Goat) have been spread and farmed by various goat farms throughout the country, it is necessary to evaluate the increase in productivity achieved. This study aims to investigate the pre-weaning growth performance of Boerka (Boer x Kacang) Crossbred Kids at different genotypes and birth types. The study was carried out experimentally using 167 Boer x Kacang crossbred kids which was arranged in a Split-Plot Design covering 3 plots of kid genotype, namely: BK (50% Boer, 50% Kacang), BBK (75% Boer, 25% Kacang) , and KBK (25% Boer, 75% Kacang), each with 3 sub-plots of kid birth types, namely single born kid (CT), twin born kid (CK-2), and triplet born kid (CK-3), all including male and female kids. The response variable that measured on pre-weaning growth performance, was observed directly by measuring birth weight (BL), 90-day-old weaning weight (BS90), and daily body weight gain (PBBH) for pre-weaning period. The data is tabulated and analyzed using software “Genstat”. The results showed that BL, BS.90, and pre-weaning PBBH of Boer x Kacang crossbred kids were influenced by genotype (P<0.01) and birth type (P<0.05) of the kids, and differed (P<0.05) between males and females kid. Male kids showed BL, BS90, and Pre-Weaning PBBH 12.88, 9.20, and 9.24% higher than female kids, respectively. Based on the genotype and birth type of the kids, the highest pre-weaning growth performance was shown by single-born male BBK kids, with BL, BS.90 and Pre-Weaning PBBH 3.32±0.33, 13.06±3.46 and 0.114±0.020 kg, respectively.